The Role of Institutions in Growth and Development - Acemoglu, Daron; Robinson, James (World Bank, Washington, DC, 2017)
In this paper authors argue that the main determinants of differences in prosperity across countries are differences in economic institutions. To solve the problem of development will entail reforming these institutions. Unfortunately, this is difficult because economic institutions are collective choices that are the outcome of a political process. The economic institutions of a society depend on the nature of political institutions and the distribution of political power in society. As yet, authors only have a highly preliminary understanding of the factors that lead a society into a political equilibrium which supports good economic institutions. However, it is clear that it is the political nature of an institutional equilibrium that makes it very difficult to reform economic institutions. The authors illustrate this with a series of pitfalls of institutional reforms. The author's analysis reveals challenges for those who would wish to solve the problem of development and poverty. That such challenges exist is hardly surprising and believe that the main reason for such challenges is the forces authors have outlined in this paper. Better development policy will only come when authors recognize this and understand these forces better. Nevertheless, some countries do undergo political transitions, reform their institutions, and move onto more successful paths of economic development.